Implementation of an educational intervention pilot for residents on acute care general internal medicine wards around the 'comfort measures strategy' for end of life care. (2nd January 2021) - Wynnychuk, L. A.; Otal, Damanjot; Davidson, Heather; Pyakurel, Aakriti; Stilos, Kalli (Kalliopi)
Abstract : Purpose : This multi-component educational intervention was aimed at General Internal Medicine residents' perceived self-efficacy in providing end of life care. This study also measured the uptake of the Comfort Measures Order Set. Methods : This non-randomized study was conducted over nine 4-week rotations on one General Internal Medicine ward. The intervention consisted of: 1) a didactic module, 2) presence of the Palliative Care Consult Team at General Internal Medicine rounds and, 3) provision of end of life care educational materials. Twenty learners completed a pre/post Self-Efficacy in Palliative Care Scale. Data/Results : Data revealed improved self-efficacy ratings on the overall scale, and on all three subscales of the Self-Efficacy in Palliative Care Scale. The Comfort Measures Order Set was implemented in 62% of patient deaths in the intervention group, and 51% of patient deaths in the control group, demonstrating no statistical difference between these groups. Conclusion : The uptake of the order set in both the intervention and control groups demonstrated utility in providing a clinical framework for delivering end of life care and highlighted the need for on-going education and enhancement of clinicians' self-efficacy in end of life care.